The health and sanitation status of specific low-cost housing communities as contrasted with those occupying backyard dwellings in the city of Cape Town, South Africa - Govender, Thashlin (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD)--Stellenbosch University, 2011.